Urban Development Challenges, Risks and Resilience in Asian Mega Cities - Singh, R.B (Springer, 2015)
In this book, an interdisciplinary research group of faculty members, researchers, professionals, and planners contributed to an understanding of the dynamics and dimensions of emerging challenges and risks in megacities in the rapidly changing urban environments in Asia and examined emerging resilience themes from the point of view of sustainability and public policy. The world’s urban population in 2009 was approximately 3.4 billion and Asia’s urban population was about 1.72 billion. Between 2010 and 2020, 411 million people will be added to Asian cities (60 % of the growth in the world’s urban population).